Design of a BIM Integrated Structural Health Monitoring System for a Historic Offshore Lighthouse - Michael O'Shea (Buildings, 2020)
The advent of wireless sensors and internet of things connectivity combined with increased open source cloud based digital sharing among the architecture, engineering, and construction industry has helped expand the range of applications for building information modelling. As the rate of adoption of BIM as a standard practice for planning, designing, and constructing new infrastructure increases, the research focus is moving towards other applications. Utilizing BIM in innovative ways such as for building energy performance, carbon capture, and asset management are now being explored. An area which receives less focus is the application of BIM on existing structures. This study explores the potential for implementing BIM on an existing structure for asset management and structural health monitoring. A method of integrating sensors to enhance the visualisation of structural health monitoring through BIM is developed. The study describes how monitoring data can be integrated within the BIM of an offshore lighthouse.